Podcast Berbasis Internet of Things (IoT) sebagai Media Pembelajaran Kompetensi Berbicara bagi Mahasiswa Pendidikan Bahasa & Sastra Jawa FBS UNNES - widagdo, sungging (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This research was conducted to solve problems related to the Javanese speaking skills of PBSJ FBS UNNES students. For this reason, the development of IoT-based teaching media through podcasts is believed to be able to overcome these learning problems. Moreover, the development of the era provides space for the growth of information technology as a teaching medium that is easily accessible. Therefore, the formulation of this problem is proposed to answer the validity of research and development of IoT-based teaching media in the Javanese language achieved through R & D adaptation of the Dick, Carey, & Carey model. The results of this study are as follows. (1) IoT media speaking Javanese is able to answer the needs of research targets related to writing skills, creative power, and imagination. (2) Based on the validity test, satisfactory content validity was obtained for the Java language-speaking IoT media. For this reason, the product of this research can be used as teaching material, teaching media, theoretical foundation, as well as a reference for lecturers, students, or other researchers.